Beginning Restorative Activities Very Early: Implementation of an Early Mobility Initiative in a Pediatric Onco-Critical Care Unit - Ghafoor, Saad; Fan, Kimberly; Williams, Sarah; Brown, Amanda; Bowman, Sarah; Pettit, Kenneth L.; Gorantla, Shilpa; Quillivan, Rebecca; Schwartzberg, Sarah; Curry, Amanda; Parkhurst, Lucy; James, Marshay; et al. (Frontiers in Oncology, 2021)
Introduction: Children with underlying oncologic and hematologic diseases who require critical care services have unique risk factors for developing functional impairments from pediatric post-intensive care syndrome (PICS-p). Early mobilization and rehabilitation programs offer a promising approach for mitigating the effects of PICS-p in oncology patients but have not yet been studied in this high-risk population. Methods: We describe the development and feasibility of implementing an early mobility quality improvement initiative (BRAVE) in a dedicated pediatric onco-critical care unit. Our primary outcomes include the percentage of patients with consults for rehabilitation services within 72 h of admission, the percentage of patients who are mobilized within 72 h of admission, and the percentage of patients with a positive delirium screen after 48 h of admission. Results: Between January 2019 and June 2020, we significantly increased the proportion of patients with consults ordered for rehabilitation services within 72 h of admission from 25% to 56% (p<0.001), increased the percentage of patients who were mobilized within 72 h of admission to the intensive care unit from 21% to 30% (p=0.02), and observed a decrease in patients with positive delirium screens from 43% to 37% (p=0.46). The early mobility initiative did not cause a significant increase in unplanned extubations, lead to the unintentional removal of central venous catheters, or cause injury to patient or staff. Conclusions: Our experience supports the safety and efficacy of early mobility initiatives in pediatric onco-critical care. Additional evaluation is needed to determine the effects of early mobilization on patient outcomes.